Changes in the tumor microenvironment during lymphatic metastasis of lung squamous cell carcinoma. Issue 1 (21st January 2017) - Ikemura, Shinnosuke; Aramaki, Nao; Fujii, Satoshi; Kirita, Keisuke; Umemura, Shigeki; Matsumoto, Shingo; Yoh, Kiyotaka; Niho, Seiji; Ohmatsu, Hironobu; Kuwata, Takeshi; Kojima, Motohiro; Ochiai, Atsushi; et al.
Abstract : Metastasis and growth in neoplastic lesions requires the multistep regulation of microenvironmental factors. We aimed to elucidate the microenvironmental changes in the process of lymphatic metastasis of lung squamous cell carcinoma. We examined the morphological characteristics of 102 cases of primary tumor (PT), 50 of intralymphatic tumor (ILT), 51 of lymph node (LN) micrometastasis (LN‐Mic; ≤2 mm in size), and 82 of LN macrometastasis (LN‐Mac; ≥10 mm in size). Afterwards we evaluated the expression of nine molecules (epidermal growth factor receptor, fibroblast growth factor receptor 2, CD44, aldehyde dehydrogenase 1, Podoplanin, E‐cadherin, S100A4, geminin, and ezrin) in matched PT, ILT, LN‐Mic, and LN‐Mac from 23 of these cases. The number of smooth muscle actin α‐positive fibroblasts, CD34‐positive microvessels and CD204‐positive macrophages were also examined. As a result, the mitotic index of tumor cells was significantly lower in ILT and LN‐Mic than PT and LN‐Mac ( P  <   0.001). Moreover, stromal reaction in ILT and LN‐Mic was less prominent than in PT and LN‐Mac ( P  <   0.001). Immunohistochemical study revealed that epidermal growth factor receptor expression level and frequency of geminin‐positive cells in ILT and LN‐Mic were significantly lower than in PT and LN‐Mac ( P  <   0.05). The number of stromal cells indicated by staining of CD34, CD204, and smooth muscle actin α in ILT and LN‐Mic was also significantly lower than in PT and LN‐Mac ( P  <   0.05). In lung squamous cell carcinoma, drastic microenvironmental changes (e.g., growth factor receptor expression and proliferative capacity of tumor cells and structural changes in stromal cells) occur during both the process of lymphatic permeation and the progression into macrometastases. Abstract : Hypothetical schema of lymphatic metastasis of lung SqCC. Cancer cells undergo LN metastasis while changing their proliferative capacity and EGFR expression in accordance with each step. Stromal reaction is also modulated during this process.